Sistem Supply Chain Management Berbasis Web untuk Pengelolaan Bahan Pakan dalam Mendukung Produksi Ayam Putih - Nurlia Sari; Riki Andri Yusda; Sumantri (Jurnal Sistem Informasi Akuntansi, 2026)
Feed management is an important factor in supporting successful production in chicken farming businesses. At the Giran White Chicken Farm, the feed stock recording process is still done manually, which often results in inaccurate records, delays in feed orders, and difficulties in preparing operational reports. This study aims to design and implement a web-based Supply Chain Management (SCM) system to improve the effectiveness of feed management. The research methods include observation, interviews, and documentation, while the system design uses Unified Modeling Language (UML) with application development using PHP and MySQL. The built system is tested using the black-box testing method to ensure that all system functions run according to user requirements. The results show that the implementation of the system has increased stock recording accuracy from 78% to 96%, reduced stock discrepancies from around 15% to 4%, and accelerated the report generation process from around 2 hours to ±10 minutes. With the web-based SCM system, the feed management process has become more structured, integrated, and supports faster and more accurate operational decision-making at the Giran White Chicken Farm.